Pengaruh Pemberdayaan Karyawan Terhadap Persepsi Keadilan Organisasi dan Komitmen Organisasi (Studi Kasus Pada Badan Lingkungan Hidup (BLH) Kabupaten Gianyar, Bali) - Parameswari, Anak Agung Anggita; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of employee empowerment on perceived of organizational justice and organizational commitment at the Environment Agency (BLH) Gianyar regency. This study uses quantitative research is by using observation and questionnaire to 85 respondents. The data was analysed by Structural Equation Modeling (SEM). The study finds that employee empowerment significantly affect perceived organizational justice and significant impact on organizational commitment. Furthermore, it was found that employee empowerment positively and significantly impact organizational commitment. Finally, perceived organizational justice  mediated the effect of employee empowerment on organizational commitment.
Keywords: Pemberdayaan Karyawan; Persepsi Keadilan Organisasi; Komitmen Organisasi